2018
DOI: 10.3390/ijms19051436
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D-QSAR, Pharmacophore, and Molecular Docking in the Molecular Design of Diarylpyrimidine Derivatives as HIV-1 Nonnucleoside Reverse Transcriptase Inhibitors

Abstract: Diarylpyrimidines (DAPYs), acting as HIV-1 nonnucleoside reverse transcriptase inhibitors (NNRTIs), have been considered to be one of the most potent drug families in the fight against acquired immunodeficiency syndrome (AIDS). To better understand the structural requirements of HIV-1 NNRTIs, three-dimensional quantitative structure–activity relationship (3D-QSAR), pharmacophore, and molecular docking studies were performed on 52 DAPY analogues that were synthesized in our previous studies. The internal and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Some docking studies have been performed on already available drug compounds to rank their potential for development as antiviral agents [20,21]. Studies using molecular docking have been utilized to analyze binding interactions of antiviral compounds targeting; the HIV protease [22,23], topoisomerase II DNA gyrase enzymes [24,25], and anti-cancer compounds which target histone deacetylases [26][27][28] and a range of other diseases can assist in the optimization of molecular interactions for drug design. Studies performed to explore the broad substrate binding preferences that SARS-CoV-2 M pro has would therefore significantly assist in the optimization of any lead drug compounds that are being pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Some docking studies have been performed on already available drug compounds to rank their potential for development as antiviral agents [20,21]. Studies using molecular docking have been utilized to analyze binding interactions of antiviral compounds targeting; the HIV protease [22,23], topoisomerase II DNA gyrase enzymes [24,25], and anti-cancer compounds which target histone deacetylases [26][27][28] and a range of other diseases can assist in the optimization of molecular interactions for drug design. Studies performed to explore the broad substrate binding preferences that SARS-CoV-2 M pro has would therefore significantly assist in the optimization of any lead drug compounds that are being pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Next, all of the candidate compounds were docked into the binding pocket, and 20 possible docked conformations were obtained with different scores. 36,37 Molecular modeling figure was drawn using PyMOL software (http://www.pymol.org). 38 mTOR Enzyme Assay LANCE ® ultra time-resolved fluorescence resonance energy transfer (TR-FRET) assay (Invitrogen, Carlsbad, CA, USA) was used to determine the mTOR kinase activities of all the compounds following the manufacturer's instructions, with compound GSK2126458 (Selleck, China) as positive control.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…In order to find compounds with new scaffolds, pharmacophore modeling and molecular docking were used to screen our library of 2063 small compounds in this study. 43,44 The compounds were obtained from several research groups and most of them have not been previously reported; among them, 1276 compounds were serine/threonine kinase inhibitors with structural diversity.…”
Section: Identification Of Lead Compoundmentioning
confidence: 99%